The Effectiveness of Communication Skills Training to Increase Job Satisfaction and Job Performance of Employees in Bandar Imam Petrochemical Plant in Mahshahr - Khaleghi, Shayesteh; Homaei, Rezvan (Journal of History Culture and Art Research, 2017)
The aim of this study was to determine the effectiveness of communication skills training to increase job satisfaction and job performance in employees of Bandar Imam petrochemical plant in Mahshahr in 2016. The statistical population consisted of all employees of Bandar Imam petrochemical plant in Mahshahr in 2015. 30 employees who were selected by convenient sampling constituted the sample of the study and were assigned to experimental and control groups (15=experiment and 15=control). The research employed quasi-experimental and pretest-posttest methods with control group. The tools used in this study were Fildoroso’s job satisfaction and Paterson’s job performance questionnaires. The results of the test using analysis of covariance showed that, according to the average job satisfaction in the experimental group compared to the control group, communication skills training increased job satisfaction in the experimental group. The effect or difference is equal to 0/44. According to the average job performance in an experimental group compared to the average control group, communication skills training increased job performance in the experimental groups. The effect or difference is equal to 0/46.